Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan dengan Pengungkapan Corporate Social Responsibility sebagai Variabel Moderasi pada Perusahaan Nonbank yang Terdaftar dalam Indeks LQ45 Periode 2020–2024 - Puspassari, Dewi; Arifian Rachman, Andry (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of profitability and leverage on firm value with corporate social responsibility disclosure as a moderating variable. The population comprises non-bank companies listed in the LQ45 Index for the 2020–2024 period, and 26 companies with 130 observations were selected through purposive sampling. Profitability is proxied by return on assets, leverage by the debt to assets ratio, firm value by Tobin’s Q, and corporate social responsibility by the corporate social responsibility disclosure index based on the Global Reporting Initiative standards. The data are secondary data obtained from annual reports and sustainability reports, and they were analysed using panel data regression with a moderated regression analysis approach through EViews 10. Model selection using the Chow test, the Hausman test, and the Lagrange Multiplier test resulted in the common effect model. The results show that, simultaneously, the model is statistically fit, but partially profitability does not significantly affect firm value, leverage does not significantly affect firm value, and corporate social responsibility disclosure has no significant direct effect on firm value. Corporate social responsibility disclosure is also not proven to moderate the effect of either profitability or leverage on firm value. The adjusted coefficient of determination of 23.47 percent indicates that most of the variation in firm value is explained by factors outside the model.